The Effect of the Environmental Temperature on the Adaptation to Host in the Zoonotic Pathogen Vibrio vulnificus - Hernández-Cabanyero, Carla; Sanjuán, Eva; Fouz, Belén; Pajuelo, David; Vallejos-Vidal, Eva; Reyes-López, Felipe E.; Amaro, Carmen (Frontiers in Microbiology, 2020)
Vibrio vulnificus is a zoonotic pathogen that lives in temperate, tropical and subtropical aquatic ecosystems whose geographical distribution is expanding due to global warming. The species is genetically variable and only the strains that belong to the zoonotic clonal-complex can cause vibriosis in both humans and fish (being its main host the eel). Interestingly, the severity of the vibriosis in the eel and the human depends largely on the water temperature (highly virulent at 28ºC, avirulent at 20ºC or below) and on the iron content in the blood, respectively. The objective of this work was to unravel the role of temperature in the adaptation to the host through a transcriptomic and phenotypic approach. To this end, we obtained the transcriptome of a zoonotic strain grown in a minimum medium (CM9) at 20, 25, 28 and 37°C, and confirmed the transcriptomic results by RT-qPCR and phenotypic tests. In addition, we compared the temperature stimulon with those previously obtained for iron and serum (from eel and human, respectively). Our results suggest that warm temperatures activate adaptive traits that would prepare the bacteria for host colonization (metabolism, motility, chemotaxis and the protease activity) and fish septicemia (iron-uptake from transferrin and production of O-antigen of high molecular weight) in a generalized manner, while environmental iron controls the expression of a host-adapted virulent phenotype (toxins and the production of a protective envelope). Finally, our results confirm that beyond the effect of temperature on the V. vulnificus distribution in the environment, it also has an effect on the infectious capability of this pathogen that must be taken into account to predict the real risk of V. vulnificus infection caused by global warming.